ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PENGURUSAN KARTU TANDA PENDUDUK ELEKTRONIK (KTP-EL) DI KECAMATAN RANDUDONGKAL KABUPATEN PEMALANG - Solekhah, Nur; Herwinarni, Yuniarti; Dhani, Bilal Ahmad (PERMANA, 2017)
The purpose of this study is (1) To analyze the effect of product quality on community satisfaction users of Electronic Identity Cards (KTP-el) (2) To analyze the effect of service quality on community satisfaction users of Electronic Identity Cards (KTP-el). 3) to determine the effect of product quality and service quality together on community satisfaction using Electronic Identity Card (KTP-el) in Randudongkal District, Pemalang Regency. The hypothesis in this study is 1) it is assumed that there is an influence of product quality on community satisfaction using Electronic Identity Card (KTP-el) in Randudongkal District, Pemalang Regency. 2) Allegedly there is an influence of the quality of service on community satisfaction using Electronic Identity Cards (KTP-el) in Randudongkal District, Pemalang Regency. 3) Allegedly there is an influence of product quality and service quality together on community satisfaction using Electronic Identity Card (KTP-el) in Randudongkal District, Pemalang Regency. Data Collection Techniques used in this study were questionnaire, interview, documentation and literature study methods. While the data analysis in this study is rank spearman correlation analysis, multiple correlation analysis and coefficient of determination analysis. The conclusion of this study is 1) There is a strong, positive and significant influence on product quality on community satisfaction. This is evidenced by the results of the Spearman rank correlation analysis of 0.650. The effect of product quality with community satisfaction is positive, meaning that if product quality increases, community satisfaction will increase. Conversely, if product quality decreases, community satisfaction will decrease. From the test of the significance of the Spearman rank correlation obtained a sig value of 0,000 <0,05 which means that there is a significant effect between the quality of service and community satisfaction. 2) There is a strong, positive and significant influence on the quality of service on community satisfaction. This is evidenced by the results of the Spearman rank correlation analysis of 0.621. The influence of service quality with community satisfaction is positive, meaning that if public perceptions about service quality increase, community satisfaction will increase. Conversely, if the public perception of service quality decreases, community satisfaction will decline. From the test of the significance of Spearman rank correlation, the quality of service with community satisfaction obtained a sig value of 0.000 <0.05, which means that there is a significant effect between the quality of service and community satisfaction. 3) There is a strong, positive and significant influence on product quality and service quality together on community satisfaction. This is evidenced by the results of multiple correlation analysis of 0.791. From the test of the significance of multiple correlation obtained sig value 0,000 <0,05 which means that there is a significant effect between the quality of service and community satisfaction. Keywords: Product Quality, Service Quality and Community Satisfaction